PREDICTING THE RELATIONSHIP BETWEEN SCARCITY AND SERENDIPITY INFORMATION TOWARD IMPULSE BUYING BEHAVIOR: HEDONIC SHOPPING VALUES AS MODERATOR VARIABLES - A. Prawira, Natasha A.; Sihombing, Sabrina O. (ASEAN Marketing Journal, 2021)
Manuscript type: Research article Research Aims: The purpose of this research is to predict the intervariable relationship between scarcity and serendipity information moderated by hedonic values and their influence towards online impulsive buying behavior. Design/methodology/approach: This research uses a quantitative method and uses non-probability sampling method as the data collection techniques by distributing online questionnaires. There are 330 respondents with the criteria of having made transactions at Shopee in the last three months. The data are analyzed using Structural Equation Modeling (SEM) to test the each of the hypothesis and making the conclusion. Research Findings: This study shows that the relationship between scarcity, serendipity information moderated by social shopping, adventure shopping, value shopping, relaxation shopping and idea shopping towards online impulse buying behavior Theoretical Contribution/Originality: This research makes a theoretical contribution to international business as well as the theory of consumer behavior about situational factors namely, the scarcity and chance of information as independent variables are moderated by the value of hedonic shopping, namely, social, adventure, value, relaxation and shopping ideas affecting the dependent variable, online impulsive buying Practitioner/Policy Implication: The results of this study can be used as information for PT Shopee International company management in determining online sales and marketing strategies that focus on the e-commerce marketplace Research limitation/Implications: This study uses non-probability sampling, thus the results of this study cannot be generalized to other contexts